Diagnostic and diversity of a novel secovirid affecting cassava in the Americas - Jiménez Polo, Jenyfer; Leiva Sandoval, Ana Maria; Fernandez Huaytalla, Elizabeth; Bartolini, Ida; Cuéllar, Wilmer Jose (2022)
We have developed a protocol for the detection, and characterization of pathogens in cassava (Manihot esculenta Crantz, Fam. Euphorbiaceae) widely cultivated in the tropics of Africa, Asia and Latin America. These processes guarantee the extraction of nucleic acids of high quality and yield to ensure their use in the detection of DNA and RNA viruses and the sequencing of viral genomes. An average of 2.11 μg of nucleic acids per mg of dry tissue can be obtained using silica gel as a desiccant avoiding the use of liquid nitrogen and phenol. Diverse families of viruses infect cassava, causing significant economic losses and affecting food security. In the Americas, Cassava torrado-like virus (CsTLV) belongs to the Family Secoviridae, Genus Torradovirus have been found in mixed virus infections in Colombia and Brazil, associated with severe disease symptoms in leaves and roots of cassava. In single infections CsTLV can induce leaf chlorotic spots symptoms. Using Oxford Nanopore Technology we complete the genome sequence of a field isolate of CsTLV, showing the characteristic genome arrangement of members of the genus Torradovirus. interestingly CsTLV encodes an atypical Maf / HAM1 domain that functions in eukaryotes to protect cells against mutagenesis only present in heterologous viruses of the Potyviridae family. Using this protocol, we analyzed field surveys in Colombia and a cassava country-wide collection from Peru, detecting the diverse isolates of CsTLV and the occurrence of the virus in the Americas.